Promoting accessibility for sustainable tourism: a spatial analysis of tourist attractions and public transportation networks in Bangkok - Iamtrakul, Pawinee; Chayphong, Sararad; Seo, Ducksu; Trinh, Tu Anh (City, territory and architecture, 2025)
The tourism sector plays a critical role in driving economic development. Within this domain, transportation systems are of paramount importance, facilitating connectivity between tourist attractions and shaping destination preferences. Consequently, the optimization of an efficient and integrated transportation infrastructure has the potential to substantially enhance tourism growth. This study seeks to examine the potential for strengthening the public transportation network to support and promote tourism development in Bangkok. Employing physical analysis tools that incorporate considerations of density, centrality, and accessibility within the public transportation network and its intersection with tourist attractions, geographic information systems are deployed. These systems facilitate the examination of spatial information pertaining to diverse facets of the public transportation system, employing methodologies such as kernel density estimation and network analysis, subsequently subject to statistical significance testing. The analysis unveils that locales characterized by a heightened concentration of tourist attractions occupy a central role within the public transport system, owing to their proximity to various transportation modalities, encompassing water and bus transport. However, in light of the dispersed distribution of tourist attractions across varied areas, the overall centrality of the public transport system emerges as suboptimal. This poses a substantive challenge in advancing alternative transportation systems tailored for tourism. Consequently, in regions distanced from economic hubs, vehicular reliance persists as predominant across multiple travel modes. Mitigating this challenge assumes paramount importance in fostering sustainable tourism development.